Application of the WHO nutrient profile model on food product data recorded for the Austrian project "Food in the Spotlight". (2020) - Meidlinger, Bettina; Luipersbeck, Christian; Bruckmüller, Melanie U.; Dieminger-Schnürch, Birgit; Bürger-Schwaninger, Bernadette; Spitzbart, Stefan; Schindler, Karin; Fuchs, Klemens; Wolf-Spitzer, Alexandra
Abstract: Introduction: Children are exposed to marketing of foods with a high content of energy, fat, sugar and salt on a daily basis, which can have negative consequences via increasing children's preferences for those foods. An unhealthy diet can promote obesity and other noncommunicable diseases. The objective of this scientific work was to assess the applicability of the nutrient profile model (NPM) for food products available in the Austrian market. The model was developed by the WHO Regional Office for Europe to reduce the impact of marketing to children. Material and Methods: The NPM was applied to food product information, which was recorded for the project "Food in the Spotlight" (www.lebensmittellupe.at). Food products were assigned to food categories made by the WHO and the NPM was applied to identify products, which should not be allowed to be marketed to children. As the WHO NPM is flexible and can be adapted to the national context possible adaptations of the model to the Austrian market were developed. Results: Among those product groups which were included in Food in the Spotlight 0% of cocoa (n = 89), milk drinks with additional ingredients (e.g. strawberry milk, n = 111), soup pearl croutons (n = 13), ketchups (n = 79) and pestos (n = 119), 0.4% of soft drinks (Cola, lemonade etc., n = 454), 8% of pizza and pizza-like products (n = 274), 13% of yoghurt products with additional ingredients (n = 611), 18% of sugos (n = 193), 28% of fruit and vegetable purees (n = 36) and 33% of breakfast cereals (n = 678) were found to be eligible for marketing to children. Those 0.4% of soft drinks which would be allowed are two waters flavoured with aroma. Pure products such as whole milk and yoghurts with 3.5% fat would not be allowed because they exceed the thresholds for total fat. For those products with a packaging appealing to children and adolescents almost none passed the NPM. Conclusion: Our results showed, that before the NPM can be implemented in Austria, it is important to adapt the model to national dietary guidelines. Additionally, food categories could be modified to be more suitable for the Austrian market, as some products which are common in Austria could not be easily assigned to the WHO food categories. To adapt the WHO NPM to the national context cooperation between health experts and food manufacturers is necessary.